Economic Efficiency of Management Accounting Systems - Anand, Dr.Utkarsh; Ahmed , Mariyam (International Journal of Accounting and Economics Studies, 2025)
This research aims to demonstrate and test a multifaceted method for assessing management accounting systems' efficacy. By focusing on the synergies that arise from the balanced growth of its four information dimensions, this multidimensional concept could be really important for future research and, in turn, offer fresh perspectives on management accounting. A highly prized competitive advantage for small and medium-sized businesses is the capacity to assess and control economic efficiency. Economic efficiency shows how big the indications of effective and efficient use of resources are, as well as how well the company processes, goods, and services work. The impact of the internal and external business environments must be taken into consideration while assessing and maintaining economic efficiency, as well as the variety of topic position assessments. The financial statements in financial accounting provide valuable data that helps assess how efficiently businesses are operating, which is crucial for effective management.
Keywords: Economic Efficiency; Management; Small and Medium-Sized Businesses; Return on Equity